Effects and Moderators of Triple P on the Social, Emotional, and Behavioral Problems of Children: Systematic Review and Meta-Analysis - Li, Na; Peng, Jin; Li, Yi (Frontiers in Psychology, 2021)
Background Social, emotional, and behavioral (SEB) problems in childhood are key predictors of persistent problem behaviors throughout the life course of individuals. Early parental intervention training, as an important preventive measure, plays a critical role in improving children’s SEB development. Method We conducted a systematic review and meta-analysis to analyze the intervention effects of the latest literature on Triple P (Positive Parenting Program), which is a multilevel system that provides treatment and prevention for children at risk of social, emotional, and behavioral problems via parenting approaches to enhance parents’ parenting knowledge, skills, and confidence. Since the literature on Triple P from 1970–2012 has already been systematically reviewed, this study searched the literature from 2013–2020 from the Web of Science, EBSCO, ERIC, MEDLINE, CNKI, and Triple P Evidence-Base website using multiple search strategies. This study differs from the existing research by its inclusion criteria of studies that use experimental design or quasi-experimental design. A total of 37 studies were included in the final analysis, and STATA 16.0 was used for evaluation while RevMan 5.3 for risk of bias assessment. Results The results show that Triple P can promote children’s social competence (SMD=0.274) and prevent their emotional problems (SMD=-0.254), and behavioral problems (SMD=-1.380) to a certain extent. Simultaneously, the proximal effects on parents mainly include changing negative parenting styles (SMD=-0.460) reducing parenting conflicts (SMD=-0.311), and improving parenting efficacy and self-confidence (SMD=0.419). The distal effects on parents include reducing parents’ psychological adjustment problems (SMD=-0.265), improving parent-child relationships, and reducing parent-child conflict (SMD=-0.714). However, the meta-analysis results did not show a significant effect of Triple P on improving the marital relationship quality and satisfaction of parents (SMD=0.063). Components of the program intervention, including intervention level, service delivery format, service method, and program implementation setting, as well as the children’s age were crucial moderating factors on the outcomes of Triple P. Conclusion This study systematically reviewed the latest Triple P intervention literature and found the significant effectiveness of Triple P on children’s SEB problems and parenting outcomes, as well as the moderators of the effect size.